Digital health literacy in a person-centric world. (1st September 2019) - Robbins, Dennis; Dunn, Patrick
Abstract: The digital age is beginning to impact the healthcare system. Smartphones and other devices based on cellular technology have made access to information ubiquitous among consumers throughout the world. There has been a shift from devices that collect data to systems for those medical conditions, such as atrial fibrillation. This changes the focus from health literacy to digital health literacy and the information-communication between the healthcare professional and the individual. Moving from health literacy to digital health literacy, therefore also means shifting from patients to persons and from managing health to empowering people to live a healthier life. Digital solutions will uncover an even greater tool, the engaged patient. Highlights: Digital health is changing is having an impact on the way health information and healthcare is delivered Digital health is moving from data collection devices to systems that can detect and manage chronic health conditions Digital health has the potential to make healthcare more person-centered